The astonishing adolescent upheaval in psychoanalysis / edited by Roosevelt Cassorla and Silvia Flechner. - Cassorla, Roosevelt M. S. (Roosevelt Moises Smeke); Flechner, Silvia (Routledge, Taylor & Francis Group, 2024)
"This book brings together international contributors to share insight from their theoretical and clinical work with adolescents, considering the different psychopathological responses they see in adolescent patients and how these can be worked with in analysis. Each chapter addresses a specific topic, focusing on representing the clinical realities facing psychoanalysts in treating adolescents with different types of disturbances at the psychic level. They cover a range of situations and perspectives, including discussion of maternal violence, the erotic field, self-mutilation, and social withdrawal, with a core focus on issues affecting contemporary adolescents. Bringing together a vast range of experience, The Astonishing Adolescent Upheaval in Psychoanalysis presents a new approach which re-establishes the impact of the responses of significant objects in the impasses present in narcissistic suffering. The Astonishing Adolescent Upheaval in Psychoanalysis will be of great interest to all psychoanalytic and psychodynamic clinicians working with adolescents"-- Provided by publisher.
Keywords: Adolescent analysis.